The fatal consequences of grief - Bernhard Schmidpeter (Johannes Kepler University Linz, Christian Doppler Laboratory Aging, Health and the Labor Market, 2015)
In this paper we investigate the effect of stress on the survival probability using a child's death as the triggering event. Employing a propensity score weighted Kaplan-Meier estimator, we are able to explore the associated time pattern of grief without imposing assumptions on the underlying duration process. We find a non-monotonic relationship between time and relative survival rates: decreasing for 13 years after the event and slowly reversing afterward. However, even 19 years after the event bereaved parents have significantly lower survival probabilities compared to the hypothetical case, that the event had not occurred. Investigating the main reason for this development, our results indicate that bereaved parents have a higher probability of dying from natural causes, especially circulatory diseases. Interestingly, our results reveal that bereavement has a stronger impact on fathers, while we find only modest evidence for mothers. This is a novel and surprising finding as males are in general regarded as more stress resilient than females. However, this research shows that this perception is not true.
Keywords: I12; J14; C41; 330; Bereavement; Child death; Death; Adjusted Kaplan Meier